2006
DOI: 10.1185/030079906x89838
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization versus immobilization in the treatment of acute proximal deep venous thrombosis: a prospective, randomized, open, multicentre trial

Abstract: No benefit of prescribing bed rest in patients with deep venous thrombosis could be detected in this study. Based on data available, strict bed rest for at least 5 days is not justified if adequate therapy with low molecular weight heparin and adequate compression is assured. It remains open whether patients with initial signs of pulmonary embolism might profit from a brief immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 9 publications
0
44
0
4
Order By: Relevance
“…Four studies were finally accepted for inclusion in this review (see Table 1). 6,8,9,19 We obtained additional data from one 6 of two reports. 6,20 Quality scores for the Jadad scale for these four studies ranged from 1 to 3 of a possible 5, with a mean score of 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were finally accepted for inclusion in this review (see Table 1). 6,8,9,19 We obtained additional data from one 6 of two reports. 6,20 Quality scores for the Jadad scale for these four studies ranged from 1 to 3 of a possible 5, with a mean score of 2.…”
Section: Resultsmentioning
confidence: 99%
“…9,19 Subjects in all four studies had proximal DVT and were treated as in-patients, and all received anticoagulation therapy upon diagnosis of the DVT. Two of the four studies included only patients with symptomatic DVTs 6,9 ; the others did not indicate whether the subjects had symptomatic or asymptomatic DVTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiser et al underline that the patient should stay immobilized for at least 48 to 72 hours while treated with fully therapeutic dose of anticoagulants [12]. However, Juenger et al found in a randomized multicentre trial that strict bed rest for at least 5 days is not justified if adequate therapy with LMWH and adequate compression is assured [13].…”
Section: Editorialmentioning
confidence: 99%
“…Kiser et al underline that the patient should stay immobilized for at least 48 to 72 hours while treated with fully therapeutic dose of anticoagulants [12]. However, Juenger et al found in a randomized multicentre trial that strict bed rest for at least 5 days is not justified if adequate therapy with LMWH and adequate compression is assured [13].Finally, PTS is a major chronic complication of DVT that reduces quality of life and has important socioeconomic consequences. More than one-third of patients with DVT will develop PTS, and 5% to 10% of patients will develop severe PTS, which may manifest as venous ulceration [14].…”
mentioning
confidence: 99%